Paying It Forward: The Prefigurative Politics of Record Creation - Robinson-Sweet, Anna; Caswell, Michelle (KULA)

(untitled) (University of Victoria Libraries, 2025)
Through analysis of data from interviews with people who shared their stories with two community archives, Texas After Violence Project (TAVP) and South Asian American Digital Archive (SAADA), this article examines how records creators imagine future use and users. Our findings reveal that people create records with concrete ideas of who might access their record and how they might use it. In keeping with community archives research that troubles the sharp delineation between record creator and user, we find that community archives creators are motivated by the need for representational belonging, radical empathy for their communities, and reciprocal archival imaginaries. Many of the participants in our research also describe their story's potential use as a tool for activism and advocacy. Sharing their stories with these uses in mind, participants in our research engaged in what we call prefigurative record creation, a term we use to describe how participants enacted the future they imagine for their communities by sharing their story in the present. Prefigurative record creation constitutes a political act in opposition to the misrepresentation, erasure, and violence that marginalized communities encounter in society. Recognition of prefigurative records creation as such is crucial to helping community archives understand and meet the expectations of their donors.